FishTEDB: a collective database of transposable elements identified in the complete genomes of fish. (16th January 2018) - Shao, Feng; Wang, Jianrong; Xu, Hongen; Peng, Zuogang
Abstract: Transposable elements (TEs) are important for host gene regulation and genome evolution. Consensus sequences of TEs can assist investigators in accelerating studies on TE origins, amplification, functions and evolution, as well as comparative analyses and prediction of TEs in different species. In evolution, physiology, ecology and heredity research, fish are important models. However, to date, no comprehensive resource for TE consensus sequences exists for fish. Here, we collected genome-wide data and developed a novel database, FishTEDB, including 27 bony fishes, 1 cartilaginous fish, 1 lamprey and 1 lancelet. De novo, structure-based and homology-based approaches were combined to detect TEs. The database is open-source and user-friendly, and users can browse, search and download all data. FishTEDB also provides GetORF, BLAST and HMMER tools to analyze sequences. Database URL : http://www.fishtedb.org/